The robustness of a subset selection procedure in the case of non-orthogonal analysis of variance - Sadie, A.(Annalene) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1996.